Agricultural Productivity in Colombia - Atkinson, L. Jay (Washington] U.S. Dept. of Agriculture, Economic Research Service; [for sale by the Supt. of Docs., U.S. Govt. Print. Off., 1970)
This publication by US Department of Agriculture was issued in cooperation with the Ministry of Agriculture and the National Department of Planning of Colombia. It examines Colombia's agricultural productivity between 1950 and 1970. Agricultural output rose an average of 3.3 percent annually and total output (GNP) at 4.7 percent annually between 1950-1967.
Cover title.
Bibliography: p. 99-101.
lje 03/07/17
Loans
Keywords: Agriculture; Agriculture